Influence of Continuous Spectrum Light on Morphological Traits and Leaf Anatomy of Hazelnut Plantlets - Silvestri, Cristian; Caceres, Maria Eugenia; Ceccarelli, Marilena; Pica, Aniello Luca; Rugini, Eddo; Cristofori, Valerio (Frontiers in Plant Science, 2019)
The light spectra influence growth, development and quality of plants and seedlings, that is one of the main aspects engaging the interests of private and public researchers and nursery industries. The propagation of hazelnut (Corylus avellana L.), which in the past has been held in low consideration because of the widespread use of rooted suckers directly collected in the field, today is taking on increasing interest due to the strong expansion of hazelnut cultivation. In order to improve the quality of plants and seedlings in greenhouse acclimatization, the use of LEDs (Light Emitting Diodes) during the ex vitro growth of two hazelnut cultivars (Tonda di Giffoni and Tonda Gentile Romana) was investigated. The plantlets were maintained in a growth chamber and exposed to LED systems as a primary source of illumination. Three different light spectra were used (AP673L, NS1, G2). After four weeks, morphometric and biochemical (chlorophyll and flavonoids contents, and Nitrogen Balance Index) analyses were performed. Histological analyses highlighted interesting information on leaf anatomy. The results obtained underline the importance of light modulation for hazelnut, providing useful information for ex vitro growth of hazelnut plantlets.